Deadly scents: Exposure to plant volatiles increases mortality of entomopathogenic nematodes during infection - Gaffke, Alexander M.; Shapiro-Ilan, David; Alborn, Hans T. (Frontiers in Physiology, 2022)
Plants attacked by insects commonly mobilize various defense mechanisms, including the biosynthesis and release of so-called herbivore-induced plant volatiles (HIPVs). Entomopathogenic nematodes (EPNs) can be attracted to these belowground HIPVs, which can enhance biocontrol services from EPNs. However, recent research has also demonstrated that HIPVs can induce and initiate insect immune responses, decreasing the insect’s susceptibility to pathogens and parasites. Therefore, experiments were conducted to test the impact of HIPVs on insects and EPNs during the initial stage of EPN infection. Compounds that can impact EPN attraction and infectivity such as pregeijerene, β-caryophyllene, and α-pinene, and compounds that have been determined to increase or decrease susceptibility of insects to pathogens, such as (Z)-3-hexenyl acetate, linalool, and β-ocimene, were selected. Exposure of Galleria mellonella larvae to pregeijerene, linalool, β-ocimene and α-pinene during invasion significantly increased mortality of Steinernema diaprepesi and Heterorhabditis bacteriophora after 48 hrs. Larval treatment with β-caryophyllene only increased mortality for Heterorhabditis bacteriophora. (Z)-3-hexenyl acetate did not cause differential mortality from the controls for either nematode species. In additional experiments, we found that EPNs exposed to α-pinene and linalool were more readily recognized by the insects’ immune cells compared to the control treatment, thus the observed increased mortality was likely due to HIPVs-EPN interactions with the insect’s immune system. These results show that the presence of HIPVs can impact EPN survival in the model host, G. mellonella.